Antimicrobial effect of probiotics in combination with prebiotics against Staphylococcus aureus and Listeria monocytogenes - P Rezaee; R Vahedi Shahandashti; R Kasra Kermanshahi (مجله دانشگاه علوم پزشکی گرگان, 2016)
Background and Objective: Probiotc bacteria have benefical effect on consumer health. This study was done to investigate the antimicrobial effect of several probiotic in combinations with different prebiotics against food patoghenic bacteria including Staphylococcus aureus and Listeria monocytogenes.